Hereditary Tradition: Analyzing Connections among Detective Depictions in Texts by Poe, Doyle, and King using Harold Bloom’s Revisionary Ratios Theory - Zahroh, Adiba Qonita (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
There has been a longstanding debate about the origin of detective fiction, with most recognizing Poe as its pioneer. However, there remains a need to comprehensively analyze the literary influence that spans across generations in detective fiction. This research introduces a comprehensive analysis of the literary influence that spans across generations in detective fiction, shedding light on the intricate web of connections between Edgar Allan Poe, Sir Arthur Conan Doyle, and Laurie R. King. Central to this investigation is the application of Harold Bloom’s theory of revisionary ratios, which serves as an invaluable analytical framework. Through the application of Harold Bloom’s theory of revisionary ratios, this research provides a comprehensive exploration of the enduring significance of intertextuality in shaping the detective fiction landscape. It underscores the intricate web of influences that connect Poe’s pioneering works with subsequent narratives by Conan Doyle and King. Having the enduring significance of intertextuality that shapes the detective fiction landscape, this study still offers a novel perspective on the genre’s dynamic evolution. The method involves a detailed review of revisionary ratio concepts and their implications for understanding complex literary works more thoroughly. The result reveals the enduring significance of revisionary ratios in understanding the complexities of literary works, with Edgar Allan Poe’s influence resonating in subsequent detective stories by Sir Arthur Conan Doyle and Laurie R. King.